КРІ model impact on employee motivation and competitiveness of private healthcare facilities - Stanislav Kotenko; Iana Kobushko; Iryna Heiets; Oleksandr Rusanov (Health Economics and Management Review)
The Constitution of Ukraine stipulates that an individual, his/her life, and health are the highest state social values. The authors highlighted that the health care system is the basis of social policy, national security, public health, and economic development. The current reformation of medical and legal reforms in Ukraine are fully covered by health legislation. In the context of these laws, the government promotes the development of private, communal, and state healthcare facilities. The authors noted that private medicine is snowballing in Ukraine, but the competitiveness of private health care facilities is insufficient in state medical reform. The study emphasized the absence of appropriate tools and mechanisms to motivate staff in private healthcare facilities. Based on the findings, the authors proposed introducing a set of evaluation indicators combined into a single integrated system – key performance indicators (KPIs), which would be the basis for calculating the bonus payroll. In turn, this system of material incentives should encourage medical staff to work effectively, be active, and initiative. The mechanism for developing a set of KPIs should be approved at the administration of the private health care facility. At the same time, medical workers of all levels must participate in KPIs elaborating. The indicators of medical care quality could be further used to improve healthcare, differentiated work assessment of medical staff, and healthcare facility in general, in accreditation and certification of private health care facilities. In the study, the authors formed and analyzed groups of indicators for different categories of the medical staff of private medical institutions. The obtained results showed that different bonus rates are needed to motivate employees at various levels to create an additional incentive to build a medical career. Thus, it could be argued that private healthcare facilities should develop motivation policy and strategy, revise system and forms of remuneration, improve the mechanism of motivation and incentives, focus on increasing competitiveness indicators in private medicine.